2004
DOI: 10.1007/s11664-004-0085-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu concentration on morphology of Sn-Ag-Cu solders by mechanical alloying

Abstract: The mechanical alloying (MA) process is considered an alternative approach to produce solder materials. In this study, the effect of Cu concentration in the ternary Sn-3.5Ag-xCu (x ϭ 0.2, 0.7, and 1) solder by MA was investigated. The (Cu,Sn) solid solution was precipitated as the Cu 6 Sn 5 intermetallic compound (IMC), which was distributed nonuniformly through the microstructure. The Cu 6 Sn 5 IMC, which was present in the SnAgCu solder with high Cu composition, causes the as-milled MA particle to fracture t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The detailed fabrication process of Sn3.0Ag0.5Cu solder powders by the MA technique was described elsewhere. 14 The 130 mg Cu 6 Sn 5 nanopowders were added into 9.57 gS na nd 0.3 gA g and then mixed together to form 10 gSn3.0Ag0.5Cu solders. The RMA flux (TACFLUX, Indium Corporation of America, Utica, NY) was added directly into the solder powders at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed fabrication process of Sn3.0Ag0.5Cu solder powders by the MA technique was described elsewhere. 14 The 130 mg Cu 6 Sn 5 nanopowders were added into 9.57 gS na nd 0.3 gA g and then mixed together to form 10 gSn3.0Ag0.5Cu solders. The RMA flux (TACFLUX, Indium Corporation of America, Utica, NY) was added directly into the solder powders at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Recently, Sn-Ag-Cu composite solder alloy with doping nanosized Cu 6 Sn 5 was successfully produced by the MA process. 14 An electroless Ni-P under-bump metallization (UBM) is employed to provide adhesion and acts as ad iffusion barrier between solders and Si chips. Electroless Ni-P metallization has excellent uniformity, good corrosion resistance, strong adhesion to the substrate, and superior solderability.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed fabrication process of SnAgCu solder powders was described elsewhere. 9 The pH value of the plating solution was adjusted with a 50vol.%H 2 SO 4 solution and the working temperature was maintained at 85°C. After deposition for 15 min, the EN plated specimen was immediately immersed in DI water for 2 min and then dried with alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8] Recently, mechanically alloyed SnAgCu solder alloy was successfully produced. 9 The SnAgCu solder paste was also produced by adding flux directly into mechanically alloyed powders. Recently, Ho et al reported that the small variation of Cu concentration would affect the type of IMC formed at the SnAgCu/Ni interface.…”
Section: Introductionmentioning
confidence: 99%
“…MA is a nonequilibrium process, and it is sometimes used to make Pb-free composite solder alloys with submicron homogeneity. [15][16][17] In this study, Cu 5 Zn 8 -bearing solders produced by MA are proposed to produce Zn-added solders without poor wetting properties. The wetting angles of the Cu 5 Zn 8 -bearing solders on a Cu substrate are compared with the wetting angles of bulk solder alloys with the same amount of Cu and Zn alloying elements.…”
Section: Introductionmentioning
confidence: 99%